ANALISIS TINGKAT KEBISINGAN TERHADAP AKTIVITAS BELAJAR MENGAJAR DI FAKULTAS TEKNIK UNIVERSITAS SEMARANG - Ahmad, Fahrudin; Dwi Handayani, Iryan; Heranurweni, Sri (Elektrika, 2018)
Optimal teaching or learning activities require a conducive and quiet environment because the high concentration required on its process. Campus area requires a quiet and silent environment. It is difficult for the urban areas to get a quiet campus environment. The study tries to reveal the evaluation on how the noise factors that occur during teaching and learning process. The study was conducted at Semarang University. The research method used is descriptive analytic method. Research shows that the building of engineering faculty (the A building) at Semarang University shows the proper noise level in line with the standard (School Acoustic Quality Standards). Besides, Semarang University must establish rules and policies to control the noise levels, to intensify the comfort of the lecture process. Based on the research results, the noise level on the Engineering faculty building of Semarang University has not been in line with the predetermined standard, which is more than (55 dB).Keywords: noise, lecture activities, acoustic quality standards of school buildings